Assessing Cotton Genotypes for Resistance to Aphis gossypii (Hemiptera: Aphididae) - Morando, Rafaela [UNESP]; Silva, Ivana Fernandes da; Santana, Alisson da Silva [UNESP]; Lopes Sampaio, Guilherme Sicca [UNESP]; Lourencao, Andre Luiz; Lopes Baldin, Edson Luiz [UNESP] (Oxford Univ Press Inc, 2021)
Aphis gossypii Glover (Hemiptera: Aphididae) is a polyphagous species frequently associated with the presence of sooty mold and viruses lethal to plants. The purpose of this work was to characterize possible resistance categories of cotton genotypes against A. gossypii. Initially, a preliminary test was carried out with 78 genotypes, 15 of which were selected for infestation ability assays and the determination of the cumulative aphid-day rates. Posteriorly, these genotypes were also evaluated through antixenosis and antibiosis assays. The genotypes FM 910, FM 966 LL, Moco, Gossypium hirsutum var. punctatum L. (Malvaceae), Variedade Reba = BTK-12, Deltapine, Hi-Bred, Acala 4-42, IAC PV010-1664, IAC 21, Reba B-50 PR and FMT 709 inhibited the aphid colonization. In the infestation ability assay, G. hirsutum punctatum, IAC PV010-1664 and Acala 4-42 were the least infested. In a multiple-choice assay, Deltapine Smooth Leaf and Variedade Reba = BTK-12 were significantly less infested, suggesting antixenosis. In the antibiosis assay, Gossypium arboreum L. (Malvaceae) 1 showed the lowest number of nymphs, number of nymphs per adult per day and, number of nymphs at 10 d after the birth of the first nymph in addition to reducing the reproductive period, nymphal survival, adult longevity and, developmental time. In the FM 910, the number of nymphs produced per day and, at 10 d after the birth of the first nymph decreased, which also indicated resistance. The results obtained here are unprecedented and can be explored in breeding programs to develop insect-resistant cotton cultivars.
Keywords: host plant resistance; cotton aphid; antixenosis; antibiosis